2020
DOI: 10.1159/000508633
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastases in Neuroendocrine Tumors: Molecular Pathogenesis and Implications in Clinical Practice

Abstract: Skeletal colonization is often regarded as a rare event in patients with neuroendocrine tumors (NETs) although both national registries and retrospective series report an incidence of bone metastases as high as 20% in subjects with advanced disease. While the biological mechanisms leading to bone metastatic colonization in NETs have been poorly investigated so far, key steps of osteotropic mechanisms, including the epithelial-to-mesenchymal transition, preparation of the premetastatic niche, migration of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
0
16
1
Order By: Relevance
“…By multivariable analysis, only the hepatic tumor load independently predicted OS in the present study. Although bone metastases have been previously described as a negative prognostic factor in patients with NETs [21], in our series their presence did not significantly affect clinical outcomes, possibly a consequence of low numbers of patients with bone neoplastic involvement (n = 13).…”
Section: Discussioncontrasting
confidence: 72%
“…By multivariable analysis, only the hepatic tumor load independently predicted OS in the present study. Although bone metastases have been previously described as a negative prognostic factor in patients with NETs [21], in our series their presence did not significantly affect clinical outcomes, possibly a consequence of low numbers of patients with bone neoplastic involvement (n = 13).…”
Section: Discussioncontrasting
confidence: 72%
“…This study reported 11 patients (41 cycles) treated with 177 Lu-DOTATATE, demonstrating median PFS of 21 months 22 . There have been no specific studies that have looked at the impact of other systemic treatments, for example, chemotherapy or molecular targeted treatments on bone metastases 23 …”
Section: Discussionmentioning
confidence: 97%
“…In our series, confirming this, we find only 4% of patients with metastases exclusively in the bone. Nevertheless, bone metastases from NET are known as negative prognostic factors and determine a significant decrease in progression-free survival and overall survival ( 7 , 8 ). In our study, the death risk rate of patients with synchronous BM is approximately 2.59 times the one of patients with metachronous BM.…”
Section: Discussionmentioning
confidence: 99%
“…The primary sites most frequently involved were the small intestine and pancreas, followed at a distance by the lung and rectum ( 6 ). Bone metastases can have an important impact on the patient’s quality of life and are considered negative prognostic factors of NETs ( 7 , 8 ). The sites most frequently affected are the truncal skeleton, mostly in the vertebral region, followed by the pelvic region and ribs.…”
Section: Introductionmentioning
confidence: 99%